The Shifting Importance of Competition and Facilitation Along Diversity, Environmental Severity, and Plant Ontogenetic Gradients - (:unkn) unknown (My University, 2013)
Ecological theory and empirical studies have focused heavily on the importance of competition in plant communities. Competition can help explain species coexistence, the maintenance of species diversity, and biological invasions. Competition for resources appears to be ubiquitous among coexisting organisms. This overwhelming focus on competition over the past one hundred years may have overshadowed the importance of positive interactions (facilitation). Growing near your neighbors involves competition for resources, but it also involves alteration of a shared microclimate. Neighboring plants have the capacity to increase shade, decrease air temperatures, increase humidity, and increase shallow soil moisture in their local environment. In severe environments - tundra, deserts, salt marshes - facilitation can outweigh the effects of competition. In periods of environmental severity, these benefits can prove essential. In this dissertation, I explore the importance of both competitive and facilitative interactions across gradients of environment severity, plant ontogeny, and productivity. I use an experimental manipulation of herbaceous plant diversity to manipulate the magnitude of competition and facilitation in a series of experiments in central Minnesota. I show that woody encroachment into grasslands is influenced by both competitive and facilitative interactions related to decreasing local species diversity and increasing atmospheric CO2 (Chapter 1). I show that diversity can ameliorate the microclimate to create local conditions that are cooler and more humid, and these effects can facilitate seedling growth and survival. I show that competition appears to increase as seedlings grow in size, but this size-structured change may be due more to decreasing facilitation rather than increasing competition (Chapter 2). Finally, plants may compete strongly for resources much of the time, but this can be outweighed by strong facilitation, and the interaction between the two processes can change on a day-to-day basis (Chapter 3). Finally, I use a modified Lotka-Volterra model to show how competition and facilitation may change as a function of environmental severity and productivity, and the implications of these relationships on individual plant performance and long-term community dynamics (Chapter 4). Nutrient availability, CO2 concentrations, seasonal temperatures and precipitation will likely change independently in future climate change scenarios. It is therefore essential that we have a comprehensive understanding of the positive and negative components that underlie plant interactions, to better predict how plant communities will change in the future.
Keywords: Global Change; Herbaceous; Modelling; Oak; Pine; Theory